Compressive and Flexural Strengths of Concrete Containing Ground Palm Kernel Shells as Partial Replacement of Cement - Armah, Esau Abekah; Koffi, Hubert Azoda; Amuzu, Josef K Ametefe (Journal of Modern Materials, 2020)
This study explore the possibility of using waste ground palm kernel (GPK) shells as partial replacement of cement in concrete using mechanical destructive method has been studied. The palm kernel shells were in two forms: the GPK ordinary shells and shells subjected to incomplete combustion (i.e. the GPK “fuel” shells). In the preparation of the concrete specimens the mix ratio was 1: 2: 4 (cement: sand: stone) by weight and the replacement percentage was 0%, 20%, 30%, 40%, 50% and 60% respectively. Concrete specimen were molded in both cubic and cylindrical form and its impact on the mechanical properties such as workability, compressive strength and flexural strength using destructive test method were studied. The cubic specimen were tested at 7, 28 and 60 days whiles the cylindrical specimen were tested at 7 and 28 days. Results of physical and chemical analyses suggest that GPK “fuel” shells have acceptable cementitious properties whiles GPK ordinary shells does not. Generally, the compressive and flexural strengths of concrete containing GPK shells decrease as the replacement percentage increases. However, the values of these properties increase as the period of curing increases. The optimum level of GPK shells replacement is 20% for the ordinary shells and 30% for the “fuel” shells considering compressive strength at 28 days for the cubic samples. For the flexural strength on the cylindrical specimen, up to 60% replacement of cement by GPK shells cured for 28 days has acceptable flexural strength. In spite of the findings that the GPK ordinary shells do not have cementitious properties, the mechanical properties on such concretes can be used in low strength constructions as pavements, walk ways and non structural domestic work at a lower cost than using cement.